(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Contextual therapies are experiential and developed within the frame of modern behavior analysis. Despite having a psychoeducational focus and being inspired by dialectic philosophy and Zen Buddhism, the dialectical behavior therapy (DBT) gathers interest of contextual therapists that wish to include its strategies as enhancement to their practice. Some DBT therapists look at modern behavior analysis as a possible scientific frame that provides more precision, control and actualization of its technology. This paper representes the first analysis of DBT, as known by the author, in relation to contextual behavioral science (CBS). It’s aimed to provide a logical analysis that allows DBT therapists to rethink their strategies from a CBS perspective, and contextual therapists to integrate DBT strategies without losing coherence with their science. We believe a CBS reasoning could help therapists integrate both approaches.